The effect of eye dominancy on patients' cooperation and perceived pain during photorefractive keratectomy - Zarei-Ghanavati, Siamak (J Curr Ophthalmol, 2019)
PURPOSE: To find a possible association between patients’ cooperation, perceived pain, and ocular dominance in patients who undergo photorefractive keratectomy (PRK). METHODS: One hundred-one eligible candidates for PRK refractive surgery were recruited. Preoperative exams were performed for all patients, and the dominant eye was specified. The surgeon was unaware about which eye was dominant. After surgery, the surgeon completed a cooperation score form for each patient. Ocular cyclotorsion, cooperation, and perceived pain scores were compared between the first-second eye surgeries and between dominant-non-dominant eyes surgeries. RESULTS: The dominant eye was the right eye in 68 patients and the left eye in 33 patients. First, eye surgery was performed on the dominant eye in 56 patients and on the non-dominant eye in 45 patients. Cooperation score and perceived pain were not significantly different between the first and second eye surgeries (P = 0.902 and P = 0.223, respectively), but cyclotorsion was more in the second eye (P = 0.031). Cooperation score, pain score, and cyclotorsion were not significantly different between dominant and non-dominant eye surgeries (P = 0.538, P = 0.581, and P = 0.193, respectively). Also, there was no correlation between cooperation score and duration of the surgery for the first or second eye (P = 0.12 and P = 0.78). CONCLUSION: During PRK surgery, the patients’ cooperation and perceived pain did not seem to be associated with eye laterality or dominancy.